Neutral or Negative?: Sentiment Evaluation in Reviews of Hosting Services - Santos, Gustavo; Santos, Marcelo; Mota, Vinícius FS; Benevenuto, Fabricio; Silva, Thiago H (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2018)
Sharing economy represents activities between people to obtain, provide, or share access to goods and services, coordinated by online services. Airbnb and Couchsurfing are examples of sharing economy, where users offer hosting service in their own houses to the public. In both services, guests can review accommodations. In hosting services of the sharing economy, there is personal contact between those who offer and contract the accommodation, which can affect users' decision to make negative reviews. This is because negative reviews can damage the offered services. To evaluate this issue, we collected reviews from two sharing economy platforms, Airbnb and Couchsurfing, and from one platform of the formal economy that works mostly with hotels, Booking.com, for some cities in the United States and Brazil. We performed a sentiment analysis in the shared texts and found that reviews in the sharing economy tend to be more favorable than those in the formal economy. This can represent a problem in those systems, as an experiment with volunteers performed in this study suggests. In addition, we present some of the main features of these comments, as well as a proposal on how to exploit the results obtained.